2020
DOI: 10.1007/s00429-020-02084-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of γ-aminobutyric acid and glutamate/glutamine in the lateral prefrontal cortex with patterns of intrinsic functional connectivity in adults

Abstract: This study examined how levels of neurotransmitters in the lateral prefrontal cortex (LPFC), a region underlying higherorder cognition, are related to the brain's intrinsic functional organization. Using magnetic resonance spectroscopy (MRS), GABA+ and Glx (glutamate + glutamine) levels in the left dorsal (DLPFC) and left ventral (VLPFC) lateral prefrontal cortex were obtained in a sample of 64 female adults (mean age = 48.5). We measured intrinsic connectivity via resting-state fMRI in three ways: (a) via see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Although we found perceived stress to be related to GABA levels in the left DLPFC but not to RSFC with the left DLPFC voxel seed, we did observe a significant negative relationship between GABA levels in the left DLPFC and RSFC between the left DLPFC voxel and the left LPFC node of the CEN. The LPFC includes the DLPFC, the ventrolateral prefrontal cortex (VLPFC) and frontal eye fields ( 59 ) and GABA+ levels in the DLPFC and VLPFC have been shown to be positively correlated ( 60 ); thus, it would be expected to find an association of left DLPFC GABA with connectivity between the left DLPFC and the left LPFC node. Previous research has shown that GABA concentrations in the mPFC are associated with between-network anticorrelations of the DMN and CEN but that DLPFC GABA concentrations did not play a significant role in between-network interactions ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we found perceived stress to be related to GABA levels in the left DLPFC but not to RSFC with the left DLPFC voxel seed, we did observe a significant negative relationship between GABA levels in the left DLPFC and RSFC between the left DLPFC voxel and the left LPFC node of the CEN. The LPFC includes the DLPFC, the ventrolateral prefrontal cortex (VLPFC) and frontal eye fields ( 59 ) and GABA+ levels in the DLPFC and VLPFC have been shown to be positively correlated ( 60 ); thus, it would be expected to find an association of left DLPFC GABA with connectivity between the left DLPFC and the left LPFC node. Previous research has shown that GABA concentrations in the mPFC are associated with between-network anticorrelations of the DMN and CEN but that DLPFC GABA concentrations did not play a significant role in between-network interactions ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the neurochemical balance between excitation and inhibition has been suggested to play a key role in brainwide network interactions ( 40 ). Human MRS studies have linked Glu and GABA concentrations at rest with functional connectivity as measured by resting-state functional magnetic resonance imaging (rs-fMRI) ( 41 44 ), consistent with the role of glutamatergic excitation and GABAergic inhibition in neural dynamics.…”
Section: Introductionmentioning
confidence: 73%
“…Here, the mean rsFC was controlled since it can reduce positive biases when the global signal regression is not performed for the rsFC calculation (Glasser et al, 2018; Smith et al, 2011). Glu served as the control metabolite for GABA, and vice versa, in the primary analysis (Wang et al, 2020). Additional tests were done with tCr and NAA as control metabolites or without control metabolites (reported in Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Duncan and colleagues concluded that the rsFC between regions, especially within the default mode network (DMN), is positively correlated with the Glu level and negatively correlated with the GABA level in the investigated DMN MRS voxel (Duncan, Wiebking, & Northoff, 2014). However, the generalized hypothesis of a region-independent relationship between local neurotransmitter levels and rsFC was challenged by rsfMRI-MRS studies focusing on regions outside the DMN, such as the left dorsal and left ventral lateral prefrontal cortex (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%